A multimorbidity nurse practitioner-led clinic: Evaluation of health outcomes. Issue 4 (August 2020) - Bonner, Ann; Havas, Kathryn; Stone, Cassandra; Abel, Jennifer; Barnes, Maureen; Tam, Vincent; Douglas, Clint
Abstract: Background: Healthcare services for people living with multiple chronic diseases have traditionally been organised around each condition, an approach which is neither resource-efficient nor convenient or effective for patients. The integrated nurse practitioner service reported here was developed to optimise patient experience and outcomes within a chronic disease self-management framework. Aim: To evaluate patient outcomes following attendance at an integrated chronic disease nurse practitioner clinic for multimorbidity. Methods: A prospective service evaluation of adults with any combination of chronic kidney disease, diabetes and/or heart failure between June 2014 and December 2017. Demographic and clinical outcomes at entry and after 12 months of clinic attendance were collected from health records of all patients ( n = 162); a subgroup also completed health-related quality of life and self-efficacy measures at entry and 12 months follow-up ( n = 106). Findings: Patients attending the clinic had complex needs and poor health-related quality of life. Despite the complexity of their health problems, as a cohort blood pressure was well-controlled and self-efficacy for chronic disease management was relatively high. Over the first 12 months of integrated nurse practitioner care, there were large improvements in physical aspects of health-related quality of life and many patients achieved reductions in body mass index. Use of hospital inpatient and emergency services also decreased. Discussion: Nurse practitioner-led services have the potential to reduce treatment burden and deliver integrated chronic disease management. Conclusions: The multimorbidity clinic has improved health outcomes in this patient cohort and offers a model for enhanced primary care.